Strategi Peningkatan Kompetensi Sumber Daya Manusia Pendidikan - junaris, imam (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2017)
ABSTRACT: Educators and education personnel are the key human resources that are key to the success of educational institutions, therefore their competence must be developed continuously according to the demands and changes in the development of education. To have and prepare competent and professional educators and education personnel in their performance, educational institutions are required to apply leadership by implementing good strategies through disciplined coaching, motivation, rewards and perceptions. Guidance and development of competence, profession and career of educators and education personnel can be implemented through various strategies in the form of education and training, among others; In-house training, internship programs, school partnerships, distance learning, tiered training and specialized training, short courses at colleges or other educational institutions, internal coaching by schools, and advanced study education.